Inductive Role of Collagen Type IV During Nephrogenesis in Mice - Jalali, Mehdi; Nikravesh, Mohammad Reza; Moeen, Abbas Ali; Karimfar, Mohammad Hassan; Saidinejat, Shahin; Mohammadi, Shabnam; Rafighdoost, Houshang (Urology Journal, 2009)
Introduction: During nephrogenesis, transition of mesenchyme to the epithelium of tubules and glomeruli occurs via the interaction of ureteral bud and metanephric mesenchyme. The distribution pattern of collagen type IV suggests that a regulated balance of activities is required to facilitate migration of the ureteral bud branches into the mesenchyme and to control early extracellular matrix changes during tubulogenesis. We used a specific antibody for tracing collagen type IV basement membrane during renal tubules morphogenesis. Materials and Methods: Twenty female Balb/C mice were divided randomly into 10 groups and were kept until finding vaginal plug was as an indicator of day zero of pregnancy. Twelve pregnant mice were sacrified by cervical dislocation in one of gestational days 13 to 18 and their fetuses were fixed, serially sectioned, and underwent immunohistochemical study for tracing of collagen type IV in basement membrane of glomeruli. The same processes were used for kidneys preparation on postnatal days 5, 10, 15, and 20 in newborns of 2 mothers for each day. Results: Collagen type IV showed weak reaction on day 14 of gestation in tubular basement membrane. The amount of collagen increased continuously until the following days of fetal life and of the first 5 postnatal days in basement membrane. After this period, collagen type IV reaction was not showed significant change in newborns. Conclusion: These results indicate that developmental changes in various nephron segments from most immature stages to most differentiated structures are dependent on the collagen type IV expression.